Urinary tract infections in children from the Gulf Cooperation Council countries: a literature review (2011–2022) - Albarrak, May; Al Dabbagh, Mona; Al Hashami, Hilal; Alzomor, Omar; Ghatasheh, Ghassan; Habashy, Nervana; Hassanien, Ashraf; Pérez-López, Andrés (Frontiers in Pediatrics, 2023)
Urinary tract infections (UTIs) are common healthcare-associated and community-acquired bacterial infections in children. Data on pediatric UTIs in the Gulf Cooperation Council (GCC) region (Bahrain, Kuwait, Oman, Qatar, Saudi Arabia, and the United Arab Emirates) have not been collated. Our aim is to review the published literature on the risk factors, etiology, antimicrobial susceptibility, and treatment of pediatric (aged <18 years) UTIs from healthcare and community settings in the GCC countries.